Role of Topical Corticosteroid Therapy in Various Dermatoses - Singh, Jitendra Kishore; Zanwar, Yogesh Rupram; Kumar, Jagannath; Patel, Jatin Jayeshbhai; Dube, Vineet Chandrabhushan; Sinha, Madhurendra Kumar; Biswas, Tanushree; Dharak, Ramchander; Tiwary, Pankaj; Sutariya, Priyanka Kartik (International Journal of Research in Medical Sciences, 2021)
Topical corticosteroids are the cornerstone in managing several dermatologic disorders, including plaque psoriasis.Managing plaque psoriasis warrants the use of an effective anti-inflammatory, antimitotic, antipruritic, and immunosuppressive agent, such as clobetasol propionate (CP). Recently, CP 0.025% cream received approval by United States food and drug administration (US FDA) for the treatment of moderate-to-severe psoriasis in adult patients. CP 0.025% cream has proven efficacious in chronic skin diseases, including controlling inflammation and pruritus, in various steroid-responsive dermatoses. In contrast to prior CP formulations, this novel CP 0.025% cream formulation does not contain propylene glycol, short-chain alcohols, and sorbitol-based emulsifiers, which are known contact allergens. The other beneficial attributes of this CP 0.025% cream formulation are high penetration of active ingredients and a lower degree of systemic absorption. This case series discusses the experience of using CP 0.025% cream in terms of its efficacy and safety in various dermatologic conditions.